The birth of Israel - BBC Northern Ireland; Sculthorp, Toby ([Autralia] : BBC Active, 2008)
This program provides an in-depth historical account of how the modern state of Israel was created, from both a military and geopolitical perspective. The film begins in the early years of the Zionist movement, unleashing a spectacular procession of archival footage and insider interviews--and shedding light on the Balfour Declaration, the creation and tactics of Haganah, the impact of the Holocaust on international support for a Jewish homeland, the campaigns of the 1948 war, and its legacy today
Narrated by Jeremy Bowen
Keywords: Zionism -- Palestine -- History; Jewish-Arab relations -- History -- 1917-1948; Arab-Israeli conflict -- Occupied terrorities; Palestine -- Politics and government